Effects of shading on morphology, photosynthesis characteristics, and yield of different shade-tolerant peanut varieties at the flowering stage - Wang, Jing; Yao, Rui; Sun, Zexin; Wang, Meiwen; Jiang, Chunji; Zhao, Xinhua; Liu, Xibo; Zhong, Chao; Zhang, He; Zhao, Shuli; Wang, Xiaoguang; Yu, Haiqiu (Frontiers in Plant Science, 2024)
In maize and peanut intercropping, shading emerges as a critical factor for restricting peanut growth, yield, and quality. This study investigated the impact of 30% shade on shade-tolerant (Huayu 22 (HY22) and Fuhua 12 (FH12)) and shade-sensitive (Nonghua 11 (NH11) and Nonghua 5(NH5)) peanut varieties, with non-shaded condition as the control (CK). The effects of shade stress on plant morphology, photosynthetic characteristics, dry-matter accumulation, chloroplast ultra-microstructure, yield, and quality of different shade-tolerant peanut varieties were examined.Compared to that in the control, shade stress led to an elongation of the main stem, shortening of the lateral branches, and reduction in the leaf area. However, these changes were less significant in the shade-tolerant than in the shade-sensitive peanut varieties, with minimal effect on the elongation of the main stem height and shortening of the lateral branches. Differences in leaf area became significant during the later stages of shade stress, particularly pronounced in the shade-sensitive peanut varieties. To enhance light capture by leaves, the shade-tolerant peanut varieties exhibited increased chlorophyll content and chloroplast grain-layer numbers. The decrease in the chlorophyll a/b ratio was more pronounced in the shade-tolerant than in the shade-sensitive peanut varieties, with significant differences. However, reduced activities of ribulose 1,5-biphosphate (RuBP) carboxylase/oxygenase and fructose 1,6-biphosphate aldolase (FBA) resulted in decreased net photosynthetic rates, particularly evident in the shade-sensitive peanut varieties during the late shade period. Shade stress led to decreased dry-matter accumulation, reduced weight of 100 fruits and kernels, and a significant decline in yield in the shade-sensitive cultivars. Shading also affected peanut-kernel quality. Compared with that in the control, the protein content increased and amino-acid (except cysteine) content decreased in the shade-tolerant cultivars. Under shade stress, shade tolerant peanut varieties have increased the yield by improving the photosynthetic efficiency, which provided a reference for rational selection of shade tolerant peanut varieties in maize and peanut intercropping system.